Implementasi Pembelajaran Tahsin Al-Qur’an Di MDTA Darul Muttaqin Bojonegara - Masruroh (4, 2025)
This study aims to describe the implementation of Tahsin Al-Qur'an learning at MDTA Darul Muttaqin Bojonegara, including the planning, implementation, and evaluation processes, as well as the supporting and inhibiting factors in its implementation. This study uses a qualitative approach with descriptive methods, because it seeks to describe in depth the reality of Tahsin learning in the madrasah environment. Data collection techniques were carried out through observation, interviews, and documentation of Tahsin teachers, the madrasah principal, and students. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that Tahsin learning at MDTA Darul Muttaqin Bojonegara is implemented in a structured and continuous manner. In the planning stage, teachers develop the Tahsin curriculum and materials according to the students' ability levels. The implementation stage is carried out using the talaqqi method, musyafahah, and repeated practice that emphasizes the accuracy of makhraj and the application of tajwid laws. Evaluation is carried out periodically through assessments of reading practices and students' religious attitudes. The successful implementation of Tahsin learning is supported by the commitment of teachers, the support of the madrasah principal, and the active role of parents. Despite obstacles such as differences in student abilities and limited learning time, the learning process remains effective thanks to the personal approach and dedication of the teaching staff. Overall, the implementation of Tahsin Al-Qur'an learning at MDTA Darul Muttaqin Bojonegara has been able to improve students' ability to read the Qur'an in a tartil and correct manner, while simultaneously fostering a Qur'anic personality with noble morals and making the Qur'an a guide for life. Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi pembelajaran Tahsin Al-Qur’an di MDTA Darul Muttaqin Bojonegara, meliputi proses perencanaan, pelaksanaan, dan evaluasi, serta faktor pendukung dan penghambat dalam penerapannya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, karena berupaya menggambarkan secara mendalam realitas pembelajaran Tahsin di lingkungan madrasah. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi terhadap guru Tahsin, kepala madrasah, dan peserta didik. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran Tahsin di MDTA Darul Muttaqin Bojonegara dilaksanakan secara terstruktur dan berkesinambungan. Pada tahap perencanaan, guru menyusun kurikulum dan materi Tahsin sesuai tingkat kemampuan siswa. Tahap pelaksanaan dilakukan dengan metode talaqqi, musyafahah, dan latihan berulang yang menekankan ketepatan makhraj serta penerapan hukum tajwid. Evaluasi dilakukan secara berkala melalui penilaian praktik membaca dan sikap religius peserta didik. Keberhasilan implementasi pembelajaran Tahsin ini didukung oleh komitmen guru, dukungan kepala madrasah, serta peran aktif orang tua. Meskipun terdapat kendala seperti perbedaan kemampuan siswa dan keterbatasan waktu belajar, proses pembelajaran tetap berjalan efektif berkat pendekatan personal dan semangat pengabdian tenaga pendidik. Secara keseluruhan, implementasi pembelajaran Tahsin Al-Qur’an di MDTA Darul Muttaqin Bojonegara mampu meningkatkan kemampuan membaca Al-Qur’an peserta didik secara tartil dan benar, sekaligus menumbuhkan kepribadian Qur’ani yang berakhlak mulia dan menjadikan Al-Qur’an sebagai pedoman hidup.